Physiological responses to self-paced exercise: effort-matched comparisons across running and rowing modalities - Edwards, A. M.; Lander, P. J. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: The purpose of this study was to examine whether or not physiological responses to self-pacing are similar across different exercise modalities where the rating of perceived exertion (RPE) is matched. METHODS: Ten recreationally active adult male subjects completed baseline tests of peak oxygen uptake (.VO2) and subsequently on two separate occasions performed 20-min exercise bouts at RPE 15 (Hard) on both a motorized treadmill and a rowing ergometer. RESULTS: Mean relative work intensity (% of baseline peak (.VO2) for treadmill running was significantly higher than for rowing (86.1% vs. 83.7%) CONCLUSION: The elevated relative exercise intensity and physiological responses to motorized treadmill running suggests greater work outputs can be accomplished in this modality for the same perceived effort compared to rowing among recreationally active participants.